Panel summary: Achieving greater impact from investments in medicine in Canada - Gauvin, Francois-Pierre; McKinlay, J; Moat, KA; Alam, S (My University, 2019)
A thematic summary of what was learned from the citizen panel on achieving greater impact from investments in medicine in Canada, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: investments; medicine; Canada